Award "retired" over R. A. Fisher's links to eugenics. Issue 4 (29th July 2020) - Tarran, Brian
Abstract : COPSS ends Fisher Award and Lecture following international protests against racism and discrimination Abstract : Award "retired" over R. A. Fisher's links to eugenics; Sewage not going to waste in tracking Covid‐19; Santa Cruz bans predictive policing technology.